2006
DOI: 10.1136/pgmj.2005.038984
|View full text |Cite
|
Sign up to set email alerts
|

Chickenpox, chickenpox vaccination, and shingles

Abstract: Chickenpox in the United Kingdom, where vaccination is not undertaken, has had a stable epidemiology for decades and is a routine childhood illness. Because of vaccination, chickenpox is now a rarity in the USA. In the UK vaccination is not done because introduction of a routine childhood vaccination might drive up the age at which those who are non-immune get the illness (chickenpox tends to be more severe the older you are), and the incidence of shingles may increase. The United Kingdom is waiting to see wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
(9 reference statements)
0
13
0
Order By: Relevance
“…1 Other shorter term studies have also reported increases in HZ incidence. 42,43 The overall numbers of HZO cases with eye involvement combines both the overall increase in HZ cases and the increase in the rate of HZO with eye involvement within those HZ case (1.70 fold increase in HZ X 1.23 increase in HZO with eye involvement in HZ = 2.1 fold increase in numbers of HZO eye cases per year between 1980 and 2007).…”
Section: Discussionmentioning
confidence: 99%
“…1 Other shorter term studies have also reported increases in HZ incidence. 42,43 The overall numbers of HZO cases with eye involvement combines both the overall increase in HZ cases and the increase in the rate of HZO with eye involvement within those HZ case (1.70 fold increase in HZ X 1.23 increase in HZO with eye involvement in HZ = 2.1 fold increase in numbers of HZO eye cases per year between 1980 and 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The universal vaccination is currently a widely debate subject, with objections[13,20,21] and defenders[22,23], including clinical and cost-effectiveness aspects [24-27]. …”
Section: Discussionmentioning
confidence: 99%
“…A vaccine against herpes zoster and post-herpetic neuralgia is currently being developed, and it is not well known about how this may influence the possible effect of varicella immunisation on herpes zoster and, as a result, on the indications and effectiveness of the herpes zoster vaccine[13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…The incubation period is from 14 to 16 days (range [10][11][12][13][14][15][16][17][18][19][20][21]. This may be prolonged up to 28 days in immunocomprimised patients and in individuals who have received IVIG.…”
Section: Transmissionmentioning
confidence: 99%
“…and bacterial skin superinfection and septicaemia [2]. Reactivation of the latent virus causes herpes zoster [7,13].…”
Section: Morbidity and Mortalitymentioning
confidence: 99%